Utilization of Arabic Animated Films to Enhance Vocabulary Mastery (Mufrodāt) at SMP Islam Ar-Raafi’ Makassar - Muwafiqah Azizah Chamanda; Hamka Ilyas; Asriyah Asriyah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This study aims to analyze the process, identify supporting and inhibiting factors, and formulate solutions to the obstacles in utilizing Arabic animated films to enhance the vocabulary mastery (mufradāt) of seventh-grade students at SMP Islam Ar-Raafi’ Makassar. This research employs an action research design with an applied research approach. The research subjects consist of seven seventh-grade students. Data were collected through observation, interviews, and documentation. The findings indicate that the use of Arabic animated films makes a significant contribution to improving students’ vocabulary mastery. This medium offers high visual and auditory appeal, facilitating comprehension and retention of the material. The learning process was carried out through the stages of planning, implementation, observation, and reflection in each cycle, with continuous improvements based on field findings. Supporting factors include the availability of multimedia equipment, teacher support, and students’ learning interest. Inhibiting factors involve time constraints, limited teacher training in the use of digital media, and technical obstacles such as power outages or device malfunctions. The proposed solutions include enhancing facilities, providing teacher training, and managing learning schedules effectively. This study recommends the utilization of animated films as an effective alternative learning medium and encourages schools and teachers to integrate creative technology into the Arabic language learning process.